Radiolabeled 15-mer peptide internalization is mediated by megalin (LRP2 receptor) in a CRISPR/Cas9-based LRP2 knockout human kidney cell model - Durinova, Anna; Smutna, Lucie; Barta, Pavel; Kamaraj, Rajamanikkam; Smutny, Tomas; Schmierer, Bernhard; Pavek, Petr; Trejtnar, Frantisek (EJNMMI radiopharmacy and chemistry, 2024)
BACKGROUND: Megalin (LRP2 receptor) mediates the endocytosis of radiolabeled peptides into proximal tubular kidney cells, which may cause nephrotoxicity due to the accumulation of a radioactive tracer. The study aimed to develop a cellular model of human kidney HK2 cells with LRP2 knockout (KO) using CRISPR/Cas9 technique. This model was employed for the determination of the megalin-mediated accumulation of 68Ga- and 99mTc-labeled 15-mer peptide developed to target the vascular endothelial growth factor (VEGF) receptor in oncology radiodiagnostics. RESULTS: The gene editing in the LRP2 KO model was verified by testing two well-known megalin ligands when higher viability of KO cells was observed after gentamicin treatment at cytotoxic concentrations and lower FITC-albumin internalization by the KO cells was detected in accumulation studies. Fluorescent-activated cell sorting was used to separate genetically modified LRP2 KO cell subpopulations. Moreover, flow cytometry with a specific antibody against megalin confirmed LRP2 knockout. The verified KO model identified both 68Ga- and 99mTc-radiolabeled 15-mer peptides as megalin ligands in accumulation studies. We found that both radiolabeled 15-mers enter LRP2 KO HK2 cells to a lesser extent compared to parent cells. Differences in megalin-mediated cellular uptake depending on the radiolabeling were not observed. Using biomolecular docking, the interaction site of the 15-mer with megalin was also described. CONCLUSION: The CRISPR/Cas9 knockout of LRP2 in human kidney HK2 cells is an effective approach for the determination of radiopeptide internalization mediated by megalin. This in vitro method provided direct molecular evidence for the cellular uptake of radiolabeled anti-VEGFR 15-mer peptides via megalin.
Keywords: LRP2; Megalin; Radionephrotoxicity; Radiolabeled peptide; CRISPR/Cas9